Investigation of the photocatalytic potential of CuFe2O4 embedded on a g-C3N4 nanosheet toward malachite green (MG) dye - Manal F. Abou Taleb; Mohamed M. Ibrahim; Hafiz Muhammad Tahir Farid; Salma Aman; Naseeb Ahmad; Zeinhom M. El-Bahy (Journal of Taibah University for Science)
This study produced a hetero-structured nanocomposite consisting of CuFe2O4 (CFO) supported on g-C3N4 (g-CN) with high photocatalytic properties through hydrothermal technique. Various analytic methods were operated to investigate the physicochemical characteristics of the created nanocomposite. The photocatalytic potential of the synthesized materials was concluded with the degradation efficiency of malachite green (MG) dye under a visible source. The photocatalytic revealed that the CuFe2O4/g-C3N4 has a degradation efficiency of up to 94.79% compared to pure CuFe2O4 (66.43%) and g-C3N4 (73.95%). The stability of the composite photocatalyst was demonstrated by its consistent 89.77% efficiency across five cycles. According to the scavenger study, the photodegradation of dye species is caused by several reactive species, including holes, superoxide anion, and hydroxyl radicals. The finding indicates that the CuFe2O4/g-C3N4 exhibited high photocatalytic potential and it can also be employed in various electrical and magnetic properties.